Gross characterization of ovarian follicular population in relation to developmental stage of corpus luteum in goat - SANGHA, G K; KHERA, K S; KAPIL, KANAN (The Indian Journal of Animal Reproduction, 2023)
Studies were carried out to observe the effect of age and stage of cycle on ovarian follicular dynamics in goat ovary. 264 genitalia from non-descript goats were collected from the local slaughterhouse throughout the year and classified into immature, mature, old and pregnant on the basis of color, condition and tonicity of muscles of uteri, oviducts and ovaries. Cyclicity of mature and old animals was further adjudged on the basis of presence and stage of corpus luteum. Maximum numbers of genitalia were observed from the mature class and minimum were that from pregnant. The total number offollic_les observed was more in immature ovary as compared to mature and aged animals. Ovaries in late luteal phase of mature animals had more number of follicles per ovary as compared to early luteal and follicular phase. In aged animals, the number of follicles/ovary did not differ significantly during different stages of estrous cycle. Rate ofatresia increased in mature and old animals as compared to immature animals. Generally left ovary had more number of follicles as compared to the right.